Sosialisasi dan Partisipasi Masyarakat dalam Program Pemberdayaan Masyarakat Kelurahan (PPMK) di Kelurahan Klender - Defina, Defina (Jurnal Penyuluhan, 2015)
Village community empowerment program (PPMK) aims to overcome poverty. Socialization of the programs to the community is one of the factors that can determine the participation of the community. Obtaining a description of socialization and community involvement is the purpose of this paper. The description of community participation in PPMK that was presented by Adi was analyzed with the definition of participation (community involvement in problem identification, decision-making process to solve problem, implementation of the result and evaluation on a development activity). This paper will also present the percentage of public knowledge about the program and the percentage of community involvement in the program.Key word: poverty, empowerment, participation